Childhood memories of food and eating in lower-income families in the United States: a qualitative study - Nicklas Neuman; Karin Eli; Paulina Nowicka (BMC, 2021)
Abstract Background Childhood obesity prevention initiatives emphasize healthy eating within the family. However, family-focused initiatives may not benefit children whose families lack economic and/or social resources for home cooking and shared meals. The aim of this paper is to examine how adults talk about and make sense of childhood memories of food and eating, with particular attention to understandings of family life and socioeconomic conditions. Methods Semi-structured interviews with 49 adults in 16 families (22 parents and 27 grandparents of young children) were conducted in Oregon, United States. Most participants had experienced socioeconomically disadvantaged childhoods. The interviews were analyzed using thematic analysis, with a focus on the participants' memories of food provision, preparation, and consumption in their childhood homes. Results Two main themes were developed: (1) "Food and cohesion", with the subthemes "Care and nurturance" and "Virtue transmission through shared meals", and (2) "Food and adversity", with the subthemes "Lack and neglect" and "Restriction and dominance". The first theme captures idealized notions of food in the family, with participants recounting memories of care, nurturance, and culinary pleasure. The second theme captures how participants' recollections of neglectful or rigidly restrictive feeding, as well as food discipline tipping over into dominance, upend such idealized images. Notably, the participants alternately identified poverty as a source of lack and as an instigator of creative and caring, if not always nutritionally-ideal, feeding. Thus, they remembered food they deemed unhealthy as a symbol of both neglect and care, depending on the context in which it was provided. Conclusions Childhood memories of food and eating may express both family cohesion and family adversity, and are deeply affected by experiences of socioeconomic disadvantage. The connection between memories of food the participants deemed unhealthy and memories of care suggests that, in the context of socioeconomic disadvantage, unhealthy feeding and eating may become a form of caregiving, with nutrition considered only one aspect of well-being. This has implications for public health initiatives directed at lower-income families.